Modification of Xanthan Gum with Methyl Methacrylate and Investigation of Its Rheological Properties - Tulegenovna, K.P. (Faculty of Engineering, Universitas Indonesia, 2022)
Xanthan gum modification is considered a significant step in improving shearing, thermal degradation performance, and rheological properties. This paper investigates the rheology properties of the grafted copolymer based on xanthan gum and methyl methacrylate (XG-g-MMA), including shear stress and viscosity versus shear rate. The grafted copolymer XG-g-MMA was synthesized with different composition ratios of methyl methacrylate (MMA) (1:1.6, 1:5, and 1:8 wt.) in the presence of a potassium persulphate initiator. Fourier transform infrared spectroscopy (FTIR) characterized the obtained grafted xanthan gum (XG) to confirm the grafting process. The results of the rheology analysis show that grafted XG exhibited higher shear stress and viscosity than pure XG. However, increasing the MMA ratio increases shear stress and viscosity with increasing shear rate. In addition, the rheology measurement of the grafted copolymer showed non-Newtonian shear thinning behavior for XG and XG-g-MMA. These results can further its application in different fields, such as oil recovery and pharmaceuticals. Â© 2022. International Journal of Technology. All Rights Reserved.